CHARACTERIZATION OF MULTILAYER SUPERHYDROPHOBIC SURFACE FOR ENHANCED HIGH VOLTAGE INSULATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Superhydrophobic surfaces are widely used in electrical systems to repel moisture and enhance insulation performance. However, their exposure to environmental contaminants can degrade them over time. This study aims to characterize the properties of additional layers by analyzing their optical and structural characteristics. To evaluate the impact of multilayer deposition on their performance, several samples were prepared, then analyzed by FTIR, SEM, spectrometry, and contact angle measurement. The results indicate that increasing the number of layers enhances the structural uniformity, electrical stability, and optical transmission. These findings show the importance of multilayer structures in optimizing these surfaces, especially for electrical insulation.
Keywords: Superhydrophobic surface; Multilayer coating; Contact angle; Optical properties; Hydrophobicity enhancement; High voltage insulation